2021
DOI: 10.3389/fsoc.2021.697356
|View full text |Cite
|
Sign up to set email alerts
|

Engendered Expressions of Anxiety: Men’s Emotional Communications With Women and Other Men

Abstract: While the contemporary therapeutic discourse inveigles us to talk about our personal problems, a countervailing neo-liberal healthist discourse, aligning with conventional masculinity norms, presumes that we will manage any issues independently. This discursive tension can be difficult to navigate, especially for men confronted with still powerful traditional expectations around masculinity (e.g., self-reliance; personal control; restricted emotionality). Although qualitative research has examined how men nego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Pandemic-related stress (e.g., disease risk, ongoing economic uncertainty, loneliness, and lifestyle changes) have exacerbated men’s high-risk for depression and suicidal ideation ( Ellison et al, 2021 ). Lower prevalence rates of common mental health problems (i.e., anxiety and depression) in men should not be inferred that there is less overall experience of such ( Gough et al, 2021 ). Instead, it was suggested that reporting of psychological symptoms is limited by hegemonic masculinities related to self-reliance and not expressing emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandemic-related stress (e.g., disease risk, ongoing economic uncertainty, loneliness, and lifestyle changes) have exacerbated men’s high-risk for depression and suicidal ideation ( Ellison et al, 2021 ). Lower prevalence rates of common mental health problems (i.e., anxiety and depression) in men should not be inferred that there is less overall experience of such ( Gough et al, 2021 ). Instead, it was suggested that reporting of psychological symptoms is limited by hegemonic masculinities related to self-reliance and not expressing emotions.…”
Section: Introductionmentioning
confidence: 99%
“…In-roads are being made toward emotional intelligence in men. In-person activity-based initiatives (e.g., Men’s Sheds) have brought together mainly older men to support each other whilst mental health support online offers promise in targeting communities of men (e.g., lifestyle and ethnic groups) ( Gough et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the risk of deleterious mental health outcomes associated with men's anxiety, the gendered elements of men's experiences, including masculinities, must be adequately considered and harnessed. The field of men's anxiety should leverage existing scholarship (i.e., men's depression research) to advance theoretical models and provide empirical weight to account for men's experiences of anxiety [2,51,52]. Theoretical models of men's anxiety must detail how men describe their anxiety experiences, including their patterns for expressing and managing their anxious states.…”
Section: A Way Forward: Developing a Theoretical Model For Men's Anxietymentioning
confidence: 99%
“…Mental health resources and interventions targeting men's informal supports (i.e., partners, family and friends) are also likely to be effective in the identification, management, treatment and ultimate prevention of men's anxiety. Men have indicated a preference for informal support over formal mental health services to manage their anxiety [29], and men's intimate relationships and friendships have been shown to be a space where men can talk about anxiety [2]. Informal sources of support play a significant role in improving the knowledge surrounding mental health symptoms, and positively influencing attitudes towards formal mental health care [72,73].…”
Section: Informal Support: a Promising Intervention For Men's Anxietymentioning
confidence: 99%
See 1 more Smart Citation